EMERGING TECHNOLOGIES DEVELOPMENT: CHALLENGES FOR THE SCIENCE, TECHNOLOGY AND INNOVATION POLICIES - I. V. Danilin (Vestnik MGIMO-Universiteta, 2019)
The article discusses transformations of science, technology and innovation policy as a result of emphasis on the emerging technologies. Crisis and recession were the immediate causes for their actualization, but real reasons appear to be long-term socio-economic problems, which, in turn, form requirements for emerging technologies policies. Another group of policy factors are defined by the evolution of innovation processes, including rise of innovation ecosystems and growing importance of technology diffusion. New tasks required policy transformations, with important experiments realized within technological programs like Industrie 4.0. Among key policy trends was creation of new institutions that provide, in addition to research and development, communication of actors, formation of ecosystems and clusters in the area of emerging technologies. Another focus was technology diffusion through standards, specialized platforms and related institutions. These novelties face serious challenges. Traditional policy instruments do not correlate with the needs of new actors and processes, resulting in inefficiency of efforts. Another challenge is globalization, also growing interdependencies of innovation systems. Given the scale of expected changes, there is a need for both increased coordination of government efforts, as well as increased coherence and convergence of science, technology and innovation policy with related areas, including social policy. The latter is especially important due to the human capital and social dimensions of emerging technologies development and diffusion. In turn, these changes will require new approaches to the political process in science and technology area, including improvements in anticipatory governance practices and search for new, innovative solutions.